2021
DOI: 10.1111/his.14535
|View full text |Cite
|
Sign up to set email alerts
|

In‐situ follicular neoplasia: a clinicopathological spectrum

Abstract: In-situ follicular neoplasia: a clinicopathological spectrum Aims: In-situ follicular neoplasia (ISFN) occurs in approximately 2-3% of reactive lymph nodes, and is currently set apart from 'partial involvement by follicular lymphoma' (PFL). ISFN can progress to overt lymphoma, but precise parameters with which to assess this risk and its association with related diseases remain incompletely understood. The aim of this study was to explore these parameters. Methods and results: We reviewed 11 cases of ISFN and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Tamber et al, by reviewing 11 cases of ISFN, described 2 cases in lymph nodes with Castleman-like disease and with IgG4-RD respectively, suggesting that ISFN may be a marker of B-cell dysfunction. 42 The fourth case was instead an HHV8-MCD in which the reactivation and clonal expansion of interfollicular EBV-infected B cells related to the CD-induced immune dysregulation was postulated. This hypothesis is in line with that suggested by Hanson et al, who found a minor IGH rearrangement in two patients with plasma cell variant of CD in whom EBV genome copies were detected in the examined lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tamber et al, by reviewing 11 cases of ISFN, described 2 cases in lymph nodes with Castleman-like disease and with IgG4-RD respectively, suggesting that ISFN may be a marker of B-cell dysfunction. 42 The fourth case was instead an HHV8-MCD in which the reactivation and clonal expansion of interfollicular EBV-infected B cells related to the CD-induced immune dysregulation was postulated. This hypothesis is in line with that suggested by Hanson et al, who found a minor IGH rearrangement in two patients with plasma cell variant of CD in whom EBV genome copies were detected in the examined lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Of the MCD, two cases were associated with MGUS with one meeting the criteria for POEMS, whereas one was partially involved by ISFN. Tamber et al., by reviewing 11 cases of ISFN, described 2 cases in lymph nodes with Castleman‐like disease and with IgG4‐RD respectively, suggesting that ISFN may be a marker of B‐cell dysfunction 42 . The fourth case was instead an HHV8‐MCD in which the reactivation and clonal expansion of interfollicular EBV‐infected B cells related to the CD‐induced immune dysregulation was postulated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, pulmonary aspergillosis should be included in the differential diagnosis of the enlarged pulmonary nodules, which could explain the absence of enlarged intra‐abdominal lymph nodes. Furthermore, if ISFN had been considered in the differential diagnosis, a definite diagnosis would require resection 1 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, if ISFN had been considered in the differential diagnosis, a definite diagnosis would require resection. 1 ISFN does not require aggressive treatment; however, careful follow-up is needed. The rate of ISFN observed in resected lymph nodes is approximately 2%-3%, and the frequency of progression to overt FL is <5%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation